Echocardiographic evaluation of cardiac recovery after refractory out-of-hospital cardiac arrest. (September 2020) - Kalra, Rajat; Bartos, Jason A.; Kosmopoulos, Marinos; Carlson, Claire; John, Ranjit; Shaffer, Andrew; Martin, Cindy; Raveendran, Ganesh; Yannopoulos, Demetris
Abstract: Background: The mechanisms and degree of myocardial recovery during treatment with venoarterial extracorporeal membrane oxygenation (VA-ECMO) are unclear. We performed a descriptive study to evaluate myocardial recovery and changes in parameters of myocardial loading using echocardiography. Methods: We retrospectively evaluated patients with refractory ventricular tachycardia/ventricular fibrillation out-of-hospital cardiac arrest who were treated with the Minnesota Resuscitation Consortium protocol. Left ventricular ejection fraction (LVEF), end-diastolic diameter (LVEDD), end-systolic diameter (LVESD), and fractional shortening were assessed using serial echocardiography. One-way analysis of variance (ANOVA) was used to compare parameters over six hospitalization stages. Two-way ANOVA was used to compare these parameters between patients that survived the index hospitalization and those that died. Results: 77 patients had > 1 echocardiographic turndown evaluations. Thirty-eight patients survived to discharge and 39 patients died. Of 39 in-hospital deaths, 17 patients died before VA-ECMO decannulation and 22 patients died after VA-ECMO decannulation. Among all patients, LVEF improved from 9.7 ± 10.1% from the first echocardiogram after rewarming to 43.1 ± 13.1% after decannulation (p < 0.001) and fractional shortening ratio improved from 0.14 ± 0.12 to 0.31 ± 0.14 (p < 0.001). The LVEDD and LVESD remained stable (p = 0.36 and p = 0.12, respectively). Patients that died had a lower LVEF by an average of 6.93% (95% confidence interval: −10.0 to −3.83, p < 0.001), but other parameters were similar. Conclusion: Refractory cardiac arrest patients treated with VA-ECMO experience significant recovery of ventricular function during treatment. We postulate that this primarily occurs via reduction of LV preload.